Self-Awareness Deficits of Cognitive Impairment in Individuals With Schizophrenia. Really? - Raffard, Stéphane; Lebrun, Cindy; Bayard, Sophie; Macgregor, Alexandra; Capdevielle, Delphine (Frontiers in Psychiatry, 2020)
Misestimation of cognitive functioning has been largely described in individuals with schizophrenia. There is large evidence that correlations between subjectively assessed cognitive functioning and objectively determined cognitive functioning are weak in non clinical individuals and may be more closely related to other psychoaffective or clinical factors than to objective neuropsychological functioning. Surprisingly, no study to date has compared the associations between cognitive complaint and objective measures of cognitive functioning in individuals with schizophrenia and healthy controls. The main objective of this study was to 1) compare cognitive complaint between individuals with schizophrenia and non clinical controls, 2) explore the relationships between cognitive complaint and psychoaffective and clinical factors in the clinical group and 3) compare the relationships between subjective awareness of cognitive functioning and objective neuropsychological assessment in individuals with schizophrenia and non-clinical participants. In this study 30 individuals with schizophrenia and 20 non-clinical matched controls were included. In addition to objective cognitive measures and subjective cognition assessed by the Subjective Scale To Investigate Cognition In Schizophrenia, measures of psychotic symptoms, depression, and anxiety were included. Schizophrenia patients reported higher cognitive complaints in comparison with controls. In individuals with schizophrenia, cognitive complaint subscores were differently associated with depression, anxiety and negative symptoms. When depression was controlled for, the same number of correlations between self-rated measures of cognition and objective measures of cognition were found in both groups, but accuracy of self-assessment of cognition was lower in the schizophrenia group. When the schizophrenia group was divided into a high cognitive complaint group (SZ High CC) and a low cognitive complaint group (SZ Low CC), findings indicated that self-assessment of cognition in the SZ high CC was highly accurate (correlations with large effect sizes). By contrast the SZ low CC group severely misjudge their cognition. A significant proportion of patients with schizophrenia can accurately estimate their cognitive skills. Self-awareness of cognitive deficits in individuals with schizophrenia is an heterogenous phenomenon and misestimation of cognitive functioning might have been overestimated, partly due to secondary psychoaffective factors. Caution is warranted before jumping to the conclusion that all individuals with schizophrenia misjudge their cognitive functioning.